Navigating Digital Trust: How Service Quality and Brand Image Shape Loyalty in Online Travel Platforms - Suryana, Marceilla (Journal of Tourism, Hospitality and Travel Management, 2023)
In the rapidly expanding digital travel ecosystem, understanding the drivers of customer loyalty has become essential for online travel platforms (OTPs) operating in competitive markets. This study investigates the effects of service quality, brand image, and perceived value on customer trust, satisfaction, and loyalty among Indonesian users of OTPs. Drawing on relationship marketing theory and the technology acceptance framework, a conceptual model was tested using data collected from 243 respondents via an online survey. Structural Equation Modeling with Partial Least Squares (PLS-SEM) was employed to assess measurement and structural models. The findings reveal that service quality, brand image, and perceived value significantly influence trust, positively affecting satisfaction and loyalty. Satisfaction also serves as a strong direct predictor of loyalty. Furthermore, perceived value impacted trust and satisfaction, highlighting its dual role in enhancing user engagement. The study contributes theoretically by integrating trust-based and value-driven constructs in a single model while offering practical insights for platform managers to enhance user retention through consistent service delivery, strong brand positioning, and value-oriented experiences.